Pengaruh Budaya Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Moderasi Pada Perumda Air Minum Tirta Sanjiwani Kabupaten Gianyar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This study aims to analyze the impact of organizational culture on employee performance and explore the role of work motivation as a moderating variable in this relationship. The background of this research is based on the importance of creating a conducive work environment by strengthening positive organizational culture and enhancing work motivation, which are believed to improve employee productivity and work effectiveness. The study was conducted on employees of Perumda Air Minum Tirta Sanjiwani in Gianyar Regency. The sample size was determined using the Slovin formula, and data was collected through the distribution of questionnaires to selected respondents. The data analysis technique used was Moderated Regression Analysis (MRA) with a t-test to examine the significance of the relationships between variables. The findings show that organizational culture has a positive and significant impact on employee performance. Furthermore, work motivation plays a role as a moderating variable that strengthens the relationship between organizational culture and employee performance. These findings indicate that a good organizational culture can directly improve performance and will be more effective if supported by high levels of work motivation. Therefore, organizations that can build a positive culture and consistently encourage employee work motivation will achieve optimal and sustainable performance. It is essential for organizations to consider both factors in their human resource management strategies and conduct further research involving other sectors to strengthen the generalization of the findings and explore the influence of other variables on employee performance